A culturally responsive approach to disaster education in early childhood: empowering teachers in disaster-prone communities - Suharti; Ningrum, Mallevi Agustin; Hasibuan, Rachma; Khotimah, Nurul; Fitri, Ruqoyyah; Adhe, Kartika Rinakit; Saroinsong, Wulan Patria; Malaikosa, Yes Matheos Lasarus (Universitas Islam Negeri Raden Intan Lampung, 2025)
Background: Integrating disaster mitigation education into the Early Childhood Education (ECE) curriculum is a strategic effort to foster risk awareness from an early age, especially in disaster-prone areas. Objective: This study aims to strengthen teachers' competence in integrating disaster mitigation into the ECE curriculum through a local wisdom-based approach. Methods: Using a descriptive qualitative design with a participatory action method, the program uses a local wisdom-based approach to strengthen teachers' capacity in developing disaster responsive learning. The training includes disaster literacy workshops, curriculum integration, and play-based simulations tailored to the child's developmental stage. Data were collected through observation, focus group discussions, and teachers' reflective journals, then analyzed thematically. Results: These findings show a marked improvement in teachers' understanding of disaster risk reduction and their ability to integrate mitigation strategies into classroom activities. Conclusion: The incorporation of local cultural values has been shown to be effective in enhancing the role of teachers as facilitators of disaster-resilient and sustainable learning. This study highlights the importance of contextual and culture-based approaches in promoting disaster preparedness in early childhood education.